Desempenho de um veículo flex em bancada dinamométrica de chassi - Laranja, Gil Colona (2014)
Flex-fuel vehicles are equipped with Otto Cycle internal combustion engines and have the capability of functioning with more than one type of fuel, mixed at the same tank and burned in the combustion chamber simultaneously. This sort of motorization is a world pattern due to the scarcity of petroleum, the trade of several types of fuels, technology advances and the restriction imposed to gas emissions to the atmosphere. In Brazil, the Flexfuel vehicles are a reality, specially the ones using fuel with 20 to 25% anhydrous alcohol mixed with gasoline and those that use natural gas or original liquid fuel (gasoline or hydrated ethanol). The Brazilian model Fiat Siena, the object of this present scientific investigation, is equipped with a unique electronic central capable of managing the liquid or gaseous fuels. The purpose of this research was to perform a comparative analysis in terms of performance (in terms of both potency and consumption) of a tetra-fuel vehicle - using a chassis dynamometer, operating with different fuels: common gasoline, premium gasoline, Podium gasoline, ethanol or natural gas. It became necessary to develop a bench of tests and trials procedures, as well as to know the functioning of the electronic management of the vehicle under analysis. The experiments were performed at the automotive laboratory in CTGAS-ER (Center of Gas Technologies and Renewable energies) at the light of Brazilian standard ABNT, NBR 7024: Light on-road vehicles - measurement of fuel consumption. The essay results on specific fuel consumption using common gasoline, premium gasoline and Podium gasoline have shown similar results, both for urban and road driving cycles